Recurrence of atrial fibrillation after pulmonary vein isolation, should we change the energy and technique? - Ramos, Jorge Toquero; Durante-López, Alejandro; Mirelis, Jesús González; Urda, Víctor Castro; Izquierdo, Eusebio García; Sánchez, Diego Jiménez; Fernández-Lozano, Ignacio (Journal of Cardiology and Cardiovascular Medicine, 2020)
Background: Pulmonary vein isolation (PVI) is the accepted standard nowadays for atrial fibrillation (AF) ablation. The most widespread ablation techniques are cryoballoon (CB) and point-by-point radiofrequency (RF) ablation. Comparative studies between both techniques have shown their equivalence for the first ablation procedure, but no trial has explored the potential incremental benefit of crossing over the ablation technique after AF recurrence. Objective: To explore the potential incremental benefit of a crossover ablation strategy for AF recurrences, comparatively with repeating the same ablation energy used for the first procedure. Methods: Retrospective analysis of patients undergoing a second AF ablation procedure after documented AF recurrence. Patients were excluded if all 4 PV were isolated at the beginning of the second procedure or extra-PVI ablation was used for the second procedure. Crossover group (n = 16) included patients in which two different techniques were used for the first and second procedure (CB-RF or RF-CB). Control group (n = 23) for those with same ablation procedure (RF-RF of CB-CB). Acute procedure end-point was PVI of all four pulmonary veins. Patients were followed-up at 3, 6, and 12 months with an electrocardiogram and a 24 h-holter. Arrhythmia-free survival at 1 year after the second ablation procedure was studied, comparing efficiency and safety of the two approaches (crossover vs. same energy). Success was defined as freedom from AF or atrial tachycardia lasting > 30 s off antiarrhythmic drugs (AADs) Results: A cohort of 39 paroxysmal and persistent AF patients was analyzed. PVI after the second procedure was 100% in all patients in both groups. There were no baseline relevant differences between the two groups. No deaths or hospitalizations occurred during follow up (data censored at 24h moths). At 1 year, arrhythmia free-survival was significantly higher in the crossover group compared to control group [93,3% vs. 47,8%; HR 0.19 (0.06-0.66);p = 0,009]. Conclusion: Crossing the ablation technique (point-by-point radiofrequency or cryoballoon PVI) after AF recurrence significantly improved arrhythmia free-survival at one year, despite no difference in acute success (PVI isolation). Randomized controlled trials with a higher amount of patients are needed to confirm the results and widespread this approach.